Management Management of Halal Assurance System for Small and Medium Industry Products with Halal Certification - Murniyanto Murniyanto (International Journal of Southeast Asia, 2023)
As a producer, quality and food safety are absolute things that every business owner must pay attention to for the products they produce. Small and Medium Industries engaged in the snack or processed food sector that guarantee their products with halal certificates are also required to maintain the existing halal guarantee system with a system recommended by LPPOM MUI, the established halal guarantee system. This study aims to determine the implementation of the management of the halal assurance system for halal-certified small and medium industrial products in Rejang Lebong. Field research and a qualitative approach to data collection methods through interviews and documentation. The data analysis technique used is descriptive by thinking inductively to analyze data that has been collected previously and then described in order to get conclusions from the research. The producer guarantees the halalness of each material used by adjusting it to the materials previously registered with LLPOM MUI. The halal guarantee system implemented by LPPOM for small and medium industries is different from large companies. Company standards, namely halal policies, materials and products. The production process is carried out in a practical and simple way. The various components in the halal guarantee system are limited to the functions performed by business owners in carrying out their work.